AREA EFFICIENT DECIMATION FILTER BASED ON MERGED DELAY TRANSFORMATION FOR WIRELESS APPLICATIONS - Rashid, U.; Siddiq, F.; Muhammad, T.; Jamal, H. (The Nucleus, 2013)
Expected by 2014 is the 4G standard for cellular wireless communications, which will improve bandwidth, connectivity and roaming for mobile and stationary devices.4G and other wireless systems are currently hot topics of research and development in the communication field. In wireless technologies like Global System for Mobile (GSM), Digital Enhanced Cordless Telecommunications (DECT) and Wi-Fi, decimation filters are essential part of transceivers being used. This paper describes a decimation filter which is efficient in terms of both the power consumption and the area used. The architecture is based upon Merged Delay Transformation (MDT). The existing Merged Delay Transformed Infinite Impulse Response (IIR) architecture is power efficient but requires larger area. The proposed and existing filters were implemented on Field-Programmable Gate Array (FPGA). The computational cost of the proposed filter is reduced to (3N/2 + 1) and M-1 times reduction in the number of multipliers in comparison to the existing FIR filter is achieved. The power consumption and speed remain nearly the same.